Long-Term Results After Laparoscopic Lavage for Perforated Diverticulitis Purulent Peritonitis in Sweden: A Population-Based Observational Study - Andreas Samuelsson, MD; David Bock, PhD; Mattias Prytz, MD, PhD; Carolina Ehrencrona, BSc; Anette Wedin, RN; Eva Angenete, MD, PhD; Eva Haglind, MD, PhD (Annals of Surgery Open)
Objective:. To compare long-term outcomes after laparoscopic lavage with resection surgery for perforated diverticulitis, Hinchey grade III as practiced in Sweden for 3 years. Background:. Laparoscopic lavage has been studied in 3 randomized controlled trials. Long-term results indicate that additional surgery and a remaining stoma are less common after lavage compared with resection, but data from routine care and larger cohorts are needed to get a more complete picture. Methods:. LapLav is a national cohort study with nearly complete coverage of all patients operated in Sweden between 2016 and 2018. The cohort was retrieved from the national patient register by a definition based on the Classification of Diseases and Related Health Problems-10 code plus the surgical procedural code. All medical records have been reviewed and data retrieved in addition to registry data. Propensity score with inverse probability weighting was used to balance the 2 groups, that is, laparoscopic lavage vs resection surgery. Results:. Before the propensity score was applied, the cohort consisted of 499 patients. Additional surgery was more common in the resection group [odds ratio, 0.714; 95% confidence interval (CI) = 0.529–0.962; P = 0.0271]. Mortality did not differ between the groups (hazard ratio, 1.20; 95% CI = 0.69–2.07; P = 0.516). In the lavage group, 27% of patients went on to have resection surgery. Conclusions:. In Swedish routine care, laparoscopic lavage was feasible and safe for the surgical treatment of perforated diverticulitis, Hinchey grade III. Our results indicate that laparoscopic lavage can be used as a first-choice treatment.